Eu quero ser uma princesa: um olhar sobre a construção da representatividade feminina nas infâncias a partir dos filmes da Disney - Motta, Nicoli Francine da (Universidade Federal de São Carlos, 2019)
The work sought to understand how the behavior of princesses idealized by Walt Disney Animations Studios influences children from 3 to 5 years of age, in preschool. Movies were analyzed from the naive and exemplary housewife in search of the prince charming, Snow White, from 1938, to the courageous Moana, from 2016. It was found that the macho ideology in Walt Disney films was widely disseminated by both male and female characters, in the sense of reinforcing the need for women to need to be accepted by a man, molding themselves to male expectations. However, it was observed that children today are more enchanted by princesses who have control over their own lives, who have dreams and goals – the so-called “contemporary princesses”. The study enabled a reflection on how the new representations of female characters can change the children-viewers' ideals and convictions, reflecting on the transformations in the role of women over the years and teaching that there are other options for personal satisfaction besides if you find a prince charming.
I want to be a princess: a glimpse into the construction of female representation in childhood from Disney films
Keywords: Princesas; Princesses; Feminismo; Feminism; Gênero e educação; Gender and education; Educação infantil; Early childhood education; Disney; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO